Enterococcus faecalis Endocarditis and Outpatient Treatment: A Systematic Review of Current Alternatives - Laura Herrera-Hidalgo; Arístides de Alarcón; Luis E. López-Cortes; Rafael Luque-Márquez; Luis F. López-Cortes; Alicia Gutiérrez-Valencia; María V. Gil-Navarro (MDPI AG, 2020)
The selection of the best alternative for Enterococcus faecalis infective endocarditis (IE) continuation treatment in the outpatient setting is still challenging. Three databases were searched, reporting antibiotic therapies against E. faecalis IE in or suitable for the outpatient setting. Articles the results of which were identified by species and treatment regimen were included. The quality of the studies was assessed accordingly with the study design. Data were extracted and synthesized narratively. In total, 18 studies were included. The treatment regimens reported were classified regarding the main antibiotic used as regimen, based on Aminoglycosides, dual β-lactam, teicoplanin, daptomycin or dalbavancin or oral therapy. The regimens based on aminoglycosides and dual β-lactam combinations are the treatment alternatives which gather more evidence regarding their efficacy. Dual β-lactam is the preferred option for high level aminoglycoside resistance strains, and for to its reduced nephrotoxicity, while its adaptation to the outpatient setting has been poorly documented. Less evidence supports the remaining alternatives, but many of them have been successfully adapted to outpatient care. Teicoplanin and dalbavancin as well as oral therapy seem promising. Our work provides an extensive examination of the potential alternatives to E. faecalis IE useful for outpatient care. However, the insufficient evidence hampers the attempt to give a general recommendation.